Comparing structured mix and random rotation procedures to teach receptive labeling to children with autism. (12th November 2019) - DiSanti, Brittany M.; Eikeseth, Svein; Eldevik, Sigmund; Conrad, Jenna M.; Cotter‐Fisher, Kortnie L.
ABSTRACT: We compared two procedures using an alternating treatments design to teach receptive labeling to children with autism. The structured mix procedure followed seven steps entailing mass trials, intermixing, and random rotation. In the random rotation procedure, we trained all stimuli from the start. Study 1 included four children with a repertoire of four to 50 receptive labels and who primarily communicated with an alternative communication device. Results showed that the two conditions were comparable for one participant, structured mix was effective and random rotation was not effective for one participant, and that both conditions were ineffective for two participants. Study 2 included five children with over 200 receptive labels in their repertoire and with vocal speech as the primary form of communication. Four participants acquired the labels in both procedures, but random rotation was more effective. Results indicate that structured mix may be more effective for participants with a limited language repertoire and random rotation is more effective for participants with a larger language repertoire.